Overview Of Adolescent Knowledge In The Impact Of Early Marriage In Boalemo Regency - Dwi Santika Putri, Ni Made; Jafar, Rahmatia; Liputo, Nur Oktaviayani; Wulansar, Ika; Arsad, Nikmatisni (Jambura Nursing Journal, 2025)
Early marriage has a number of consequences, not only limited to the impact on physical and mental health. Women and men who marry at an early age unconsciously forget their right to get an education, pursue school, and achieve their dreams. The research objects studied were teenagers in Modelomo Village, Tilamuta District, Boalemo Regency. This research aims to determine the level of knowledge of teenagers regarding the impact of early marriage. This research is quantitative research with descriptive observational type with accidental sampling technique. The sample in this study was 44 teenagers from Modelomo Village. The research results showed that the majority of respondents had a good level of knowledge, 16 respondents (36.4%), 27 respondents (61.4%), and 1 respondent less. (2.3%). This research shows that the majority of teenagers' knowledge about the impact of early marriage is still in the sufficient category, so it requires attention from various parties to increase the knowledge of young women so that the incidence of early marriage can decrease.